2009
DOI: 10.1002/chin.200915219
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: In silico Mutagenesis and Docking Studies of Pseudomonas aeruginosa PA‐IIL Lectin — Predicting Binding Modes and Energies.

Abstract: Computers in chemistry V 0380In silico Mutagenesis and Docking Studies of Pseudomonas aeruginosa PA-IIL Lectin -Predicting Binding Modes and Energies. -(ADAM, J.; KRIZ, Z.; PROKOP, M.; WIMMEROVA, M.; KOCA*, J.; J. Chem. Inf. Model. (J. Chem. Inf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Current docking programs and empirical scoring functions do not generally provide an accurate description of protein–carbohydrate binding energetics. Efforts to tackle the problem with end-point free-energy methods such as Molecular Mechanics Poisson–Boltzmann Surface Area (MM-PB/SA), Molecular Mechanics Generalized-Born Surface Area (MM-GB/SA), or Linear Interaction Energy (LIE) have also been reported with mixed success. Mishra et al have parametrized the LIE approach directly on carbohydrates but found significant overestimations of the calculated binding free energies for low-affinity binders and nonbinders . Topin et al have shown that MM-GB/SA method yields a poor correlation between the predicted and experimentally determined free energies for lectins LecB ( r 2 = 0.22) and BambL ( r 2 = 0.02) .…”
Section: Introductionmentioning
confidence: 99%
“…Current docking programs and empirical scoring functions do not generally provide an accurate description of protein–carbohydrate binding energetics. Efforts to tackle the problem with end-point free-energy methods such as Molecular Mechanics Poisson–Boltzmann Surface Area (MM-PB/SA), Molecular Mechanics Generalized-Born Surface Area (MM-GB/SA), or Linear Interaction Energy (LIE) have also been reported with mixed success. Mishra et al have parametrized the LIE approach directly on carbohydrates but found significant overestimations of the calculated binding free energies for low-affinity binders and nonbinders . Topin et al have shown that MM-GB/SA method yields a poor correlation between the predicted and experimentally determined free energies for lectins LecB ( r 2 = 0.22) and BambL ( r 2 = 0.02) .…”
Section: Introductionmentioning
confidence: 99%
“…When the protein mutant structure is not available, an in silico mutated structure may be used. 13 The prime focus of the docking software is to determine the geometry of the ligand as accurately as reported in the crystal structure. However, when predicting new binding partners, the quantification of binding affinity by the docking software is also important.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16,17 The performance of selected docking software programs for lectins with ions in the binding site was recently reported. 13 In this study, we applied docking methods to the lectin whose interaction with sugars does not involve any ions and also for saccharides that exhibited low or nonsignificant binding with RSL. 10 In summary, the study was focused on two objectives.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modeled psychrophilic structure was taken and energy minimization or geometry optimization is carried out by using the hyperchem software to optimize the molecular structure until the gradients of potential energy on atoms become negligible. For carrying out docking studies, only half of the tetrameric molecule (1BHE and 3JUR) was considered so as to skip any detrimental conditions during the substrate binding (Adam et al 2008). …”
Section: Preparation Of Proteinsmentioning
confidence: 99%